Analytical model of I-bar clasps for removable partial dentures. Issue 6 (June 2021) - Richert, Raphaël; Alsheghri, Ammar A.; Alageel, Omar; Caron, Eric; Song, Jun; Ducret, Maxime; Tamimi, Faleh
Abstract: Objective: Clasps of removable partial dentures (RPDs) often suffer from fatigue stress that leads to plastic deformation, loss of retention, and RPD failure. Recently, computer-based technologies were proposed to optimize clasp geometry design. The objective of this study was to create an analytic model of I-bar clasps for computer-aided design (CAD)-RPD. Methods: The analytical model based on mechanical laws was established to simulate I-bar clasp retention, and optimize its design. The model considered the lengths of the vertical ( L 1 ) and horizontal (L2 ) arms of the I-bar as well as the radius (r) of its half-round cross-section. The analytical model was validated with mechanical experiments evaluating the retention of cobalt–chromium (Co–Cr) clasps in vitro and compared with finite element analysis (FEA). Results: The analytical model was in good agreement with the mechanical experiments and FEA, and showed that I-bar clasp design could provide optimal mechanical performance as long as the length of arms (L1 and L2 ) do not exceed 6 mm. Clasps with L1 > 8 mm and L2 > 9 mm presented stress values exceeding the fatigue limit of Co–Cr. The proposed solution was to increase the radius of I-bar to conserve the initial mechanical performance of Co–Cr. Significance: Co–Cr I-bar clasps perform best on teeth with reduced mesiodistal dimensions (canine and premolar), and their designs could be optimized to prevent stress from reaching the yield strength and the fatigue failure limit.